Constructing hope in the Katingan River: A phenomenological analysis - Rendi Indiwara (Priviet Social Sciences Journal, 2025)
This phenomenological study examined the lived experiences of vocational high school students engaged in a project-based learning effort designed to alleviate water pollution in the Katingan River through the application of Arduino and Internet of Things (IoT) technology. The research demonstrates a significant transformation in student engagement, evolving from initial bewilderment and reliance on instructor directives to collaborative discovery, peer mentoring, and critical inquiry through observation, recording, and reflective assessment. The study employs Colaizzi’s approach to data analysis to demonstrate that interactive media and experiential learning enhance technical proficiency, ecological consciousness, social accountability, and a profound sense of ownership in the learning process. Reflection served as the fundamental process by which students derived meaning, linking technical work to real-world difficulties and community influences. The results highlight the necessity of incorporating structured reflection into vocational education to foster significant, human-centered, and transformative learning experiences.